2020
DOI: 10.3233/blc-200290
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Risk Factors Predicting Postoperative Complications in Radical Cystectomy for Bladder Cancer

Abstract: BACKGROUND AND OBJECTIVE: While radical cystectomy (RC) is the gold-standard treatment for patients with muscle-invasive bladder cancer, it is associated with a significant rate of complications. We aim to develop a prediction model to assess the risk of complications in the postoperative period using routinely collected data in the course of preoperative evaluation in patients undergoing RC for bladder cancer. METHODS: We retrospectively reviewed 508 patients who underwent RC for bladder cancer from January 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Dyslipidemia was significantly associated with any (OR 2.46, P = 0.006) and high-grade (OR 3.02, P < 0.001) gastrointestinal complications from our cohort. One recent study 21 did not show significant association between dyslipidemia and high grade postoperative complications (OR 1.40, P = 0.35). Meanwhile, another recent study 22 concluded that statins, treatment for dyslipidemia, are associated with adhesion-related complications (including small bowel obstruction) after intra-abdominal surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Dyslipidemia was significantly associated with any (OR 2.46, P = 0.006) and high-grade (OR 3.02, P < 0.001) gastrointestinal complications from our cohort. One recent study 21 did not show significant association between dyslipidemia and high grade postoperative complications (OR 1.40, P = 0.35). Meanwhile, another recent study 22 concluded that statins, treatment for dyslipidemia, are associated with adhesion-related complications (including small bowel obstruction) after intra-abdominal surgery.…”
Section: Discussionmentioning
confidence: 84%